2021
DOI: 10.1051/e3sconf/202129701065
|View full text |Cite
|
Sign up to set email alerts
|

WMLP: Web-based Multi-Layer protocols for Emergency Data Transmission in Mobile Ad Hoc Network

Abstract: Mobile Ad Hoc Network (MANET) is an Emergency transportable Ad-Hoc network, which is a significant module of the Internet of Effects and has been extensively practiced in smart transportation systems in new existences. In this proposed system using Web-based Multi-Layer protocols for Emergency Data Transmission (WMLP), Dynamic multi-priority message order management method it is used to reduce the data transmission delay in entire networks. To fulfill the real-time limitations of emergency data, we proposed WM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The proposed base-band modulators for the SDR technique narrow down the penalty gap and provide maximum operating speed with considerable complexity reduction compared to all other counter-part models. Existing studies also showed that any optimization methodologies on the receiver side greatly influence the system performance and the hardware utilization rate [35]. In most cases, an advanced multimode base modulator is preferred for its improved quality metrics with finite computational complexity trade-off.…”
Section: Reconfigurable Baseband Modulatormentioning
confidence: 99%
“…The proposed base-band modulators for the SDR technique narrow down the penalty gap and provide maximum operating speed with considerable complexity reduction compared to all other counter-part models. Existing studies also showed that any optimization methodologies on the receiver side greatly influence the system performance and the hardware utilization rate [35]. In most cases, an advanced multimode base modulator is preferred for its improved quality metrics with finite computational complexity trade-off.…”
Section: Reconfigurable Baseband Modulatormentioning
confidence: 99%
“…Additionally, generic mechanisms such as secure Neighbor Detection and randomized ROUTE REQUEST forwarding can be employed to mitigate rushing attacks. This paper aims to enhance the security of MANETs while addressing energy efficiency and environmental sustainability concerns [21]. By incorporating energy-aware route selection techniques, the mechanism prioritizes paths that minimize energy consumption, optimizing the utilization of limited energy resources in the network.…”
Section: Introductionmentioning
confidence: 99%